Antiangiogenic drugs and advanced proliferative diabetic retinopathy - Ribeiro,Jefferson Augusto Santana (2011)
Advanced diabetic retinopathy with tractional retinal detachment or persistent vitreous hemorrhage often requires surgical treatment with pars plana vitrectomy. Despite advances in vitrectomy, surgery for complications of diabetic retinopathy can be a challenge and may be impaired by intense fibrovascular proliferation. Antiangiogenic drugs have been used for the treatment of diabetic retinopathy because of their inhibitory action on vascular endothelial growth factor. In this review, we discuss aspects related to the adjuvant use of these drugs in vitrectomy for complications of diabetic retinopathy. Bevacizumab shows beneficial effects regarding the surgical technique facilitation, but its long-term benefit still needs to be studied.